2023
DOI: 10.3389/fimmu.2023.1110185
|View full text |Cite
|
Sign up to set email alerts
|

The roles of toll-like receptor 4, CD33, CD68, CD69, or CD147/EMMPRIN for monocyte activation by the DAMP S100A8/S100A9

Abstract: The S100A8/A9 heterocomplex is an abundant damage-associated molecular pattern and mainly expressed by monocytes, inflammatory activated keratinocytes and neutrophilic granulocytes. The heterocomplex as well as the heterotetramer are involved in a variety of diseases and tumorous processes. However, their detailed mode of action and especially which receptors are involved hereby remains to be fully revealed. Several cell surface receptors are reported to interact with S100A8 and/or S100A9, the best studied bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Despite the lack of a leader sequence, some of the S100 proteins are secreted via the endoplasmic reticulum (ER)/Golgi pathway, or several unconventional passive and active mechanisms [ 2 , 27 , 28 ]. When they are released into the extracellular space, certain S100 proteins exert a cytokine-like action, due to interaction with specific cell surface receptors, such as RAGE, TLR4, ErbB1, ErbB3, ErbB4, IL-10R, integrin β1, neuroplastin-β, 5-HT 1B , 4-HT 4 , SIRL-1, ALCAM, EMMPRIN, CD33, CD36, CD68, CD69, or CD146 [ 2 , 25 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Moreover, some of the released S100 proteins interact with cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the lack of a leader sequence, some of the S100 proteins are secreted via the endoplasmic reticulum (ER)/Golgi pathway, or several unconventional passive and active mechanisms [ 2 , 27 , 28 ]. When they are released into the extracellular space, certain S100 proteins exert a cytokine-like action, due to interaction with specific cell surface receptors, such as RAGE, TLR4, ErbB1, ErbB3, ErbB4, IL-10R, integrin β1, neuroplastin-β, 5-HT 1B , 4-HT 4 , SIRL-1, ALCAM, EMMPRIN, CD33, CD36, CD68, CD69, or CD146 [ 2 , 25 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Moreover, some of the released S100 proteins interact with cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that S100A8 acts as a ligand that binds to the CD147 receptor, thereby regulating various cell fates. 47 , 48 , 49 Likewise, ligand-receptor interaction analysis between cancer cells and myCAFs indicated stronger interaction of S100A8 with the CD147 receptor compared to other receptors ( Figure S4 B). In this study, we generated CD147-knockout CAFs using CRISPR-Cas9-mediated gene targeting, in which CD147 deletion significantly suppressed the expression of αSMA ( Figure 4 H).…”
Section: Resultsmentioning
confidence: 95%
“…Next, we sought to determine whether classical inflammatory and immune response-related genes were regulated by aging in a cell type-specific manner. Upset diagrams integrating the up-regulated DEGs in B cell subsets of old mice showed that the inflammatory response-related genes Igha and S100a8 were up-regulated in all B cells [ 24 , 25 ]. The immune system signaling pathway-related genes Irf8 and Zeb2 [ 26 ] were upregulated in ABC (Fig.…”
Section: Resultsmentioning
confidence: 99%